(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents the chemical elemental composition of irrigated light sierozems formed in the Fergana region and the grape varieties grown on them. Biological absorption coefficients and geochemical spectra of microelements in these soils and organs of cultivated grape varieties have been developed.